Math Questions and Answers

Start Your Free Trial

The integral of dx/x^2 sqrt(x^2 + 9) from sqrt(3) to cube root of 3 Using trigonometric substitution

Expert Answers info

Eric Bizzell eNotes educator | Certified Educator

briefcaseTeacher (K-12)

calendarEducator since 2011

write3,158 answers

starTop subjects are Math, Science, and Business

Evaluate `int_(sqrt(3))^(root(3)(3))(dx)/(x^2sqrt(x^2+9))` :

Let `x=3tanu` . Then `dx=3sec^2udu` .

Now `sqrt(x^2+9)=sqrt(9tan^2u+9)=sqrt(9(tan^2u+1))=3secu` ; also `u=tan^(-1)(x/3)` .

So ignoring the limits of integration for the moment we have:

`int (dx)/(x^2sqrt(x^2+9))=int(3sec^2udu)/(9tan^2u(3secu))`



This can be evaluated as:


Substituting for u and evaluating at the limits of integration:

`=(-sqrt(x^2+9))/(9x)|_sqrt(3)^(root(3)(3))`  ** `-csc(tan^(-1)(x/3))=sqrt(x^2+9)/x` **




check Approved by eNotes Editorial